Risk Factors for Aborted Cardiac Arrest and Sudden Cardiac Death in Children with the Congenital Long-QT Syndrome - Goldenberg, Ilan (2008)
BACKGROUND: The congenital long-QT syndrome (LQTS) is an important cause of sudden cardiac death (SCD) in children without structural heart disease. However, specific risk factors for life-threatening cardiac events in children with this genetic disorder have not been identified METHODS AND RESULTS: Cox proportional hazards regression modeling was used to identify risk factors for aborted cardiac arrest (ACA) or SCD in 3,015 LQTS children from the International LQTS Registry who were followed up from age 1 through 12 years. The cumulative probability of the combined end point was significantly higher in males (5%) than in females (1%; p<0.001). Risk factors for ACA or SCD during childhood included QTc duration >500 msec (HR=2.72 [95%CI 1.50 - 4.92]; p=0.001) and prior syncope (recent syncope [<2 years]: HR=6.16 [95%CI 3.41 - 11.15], p<0.001; remote syncope [≥2 years]: HR=2.67 [95% CI 1.22 - 5.85], p=0.01) in males, whereas prior syncope was the only significant risk factor among females (recent syncope: HR=27.82 [95%CI 9.72 - 79.60], p<0.001]; remote syncope: HR=12.04 [95%CI 3.79 - 38.26], p<0.001). β-blocker therapy was associated with a significant 53% reduction in the risk of ACA or SCD (p=0.01). CONCLUSIONS: LQTS males experience a significantly higher rate of fatal or near-fatal cardiac events than females during childhood. A QTc duration >500 msec and a history of prior syncope identify risk in males, whereas prior syncope is the only significant risk factor among females. β-blocker therapy is associated with a significant reduction in the risk of life-threatening cardiac events during childhood.